EFFECT OF DIFFERENT TRANSPLANTING METHODS ON PADDY YIELD AND ITS COMPONENTS AT FARMER’S FIELD IN RICE ZONE OF PUNJAB - T. H. Awan; M. Ahmad; M. M. Ashraf; I. Ali (Journal of Animal and Plant Sciences, 2011)
The present study was designed to study the effect of different transplanting methods in comparison with the farmer’s conventional transplanting methods at farmer’s field. Experiments were laid out in randomized complete block design (RCBD) and replicated thrice having a net plot size of 30 m x 40 m. The studies were carried out consecutively for three years during kharif season 2003, 2004 and 2005. For this study fifteen(15) locations viz; Sheikhupura (Mallian Kalan), Nankana Sahib (Warburten), Lahore (Burki), Wazirabad (Manzoorbad), Wazirabad (Rakh Bharokae), Kamonke (Ramey Farm), Noshehra Virkan, Daska, Pindi Bhattian (Sokhakea), Hafizabad (Ahmadpur Chatha), Pasroor (Poorib Klair), Gujranwala (Batala farm), Norowal (Burj). Shakar Garh (Tittarpur) and Ferozwala (Khori) were selected. The highest paddy yield (6.02 t ha-1) was produced by standard line transplanting at Nankana sahib which was statistically at par with that recorded in the same treatment at Sheikhupura and Gujranwala sites. The lowest paddy yield (3.3 t ha-1) was recorded in the treatment where nursery was randomly transplanted by the farmer in Kamoke tehsil. Data averaged across locations and years showed the highest paddy yield of 5.07 t ha-1were produced by the standard line transplanting which remained significantly different from both the other treatments (open & framer’s transplanting). The second highest value of paddy yield (4.33 t/ha) was produced by open transplanting treatment whereas farmer’s practice of random transplanting showed lowest paddy yield of 3.97 t/ha.
Keywords: Demonstrations; dissemination of rice production technology.